2015
DOI: 10.2337/db14-1924
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Hepatic miR-22-3p Expression Impairs Gluconeogenesis by Silencing the Wnt-Responsive Transcription Factor Tcf7

Abstract: Levels of miR-22-3p, a highly abundant hepatic microRNA, are abnormally increased in mouse models of insulin resistance and type 2 diabetes, yet its contribution to deregulated hepatic metabolism under diseased states is not well understood. Here, we unravel a novel link between elevated hepatic miR-22-3p expression and impaired gluconeogenesis in diabetic db/db mice via the regulation of Tcf7 (transcription factor 7). Our data demonstrate that miR-22-3p binds to the 39 untranslated region of TCF7 and downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 44 publications
3
51
0
1
Order By: Relevance
“…For example, miR-29a-c decreases hepatic glucose production in primary hepatocytes, and adenovirus-mediated overexpression of miR-29a-c in the liver improves glucose tolerance and insulin resistance of both db/db diabetic and diet-induced obese mice (17). Furthermore, miR-802, miR-214, miR-23a, miR-22, miR-378 and miR-451a have substantial effects on hepatic glucose production (15,16,(18)(19)(20)(21). Specifically, the expression levels of miR-214 were suppressed in the starvation or in diabetic conditions (18), and Gm10768 expression levels were elevated in these two settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, miR-29a-c decreases hepatic glucose production in primary hepatocytes, and adenovirus-mediated overexpression of miR-29a-c in the liver improves glucose tolerance and insulin resistance of both db/db diabetic and diet-induced obese mice (17). Furthermore, miR-802, miR-214, miR-23a, miR-22, miR-378 and miR-451a have substantial effects on hepatic glucose production (15,16,(18)(19)(20)(21). Specifically, the expression levels of miR-214 were suppressed in the starvation or in diabetic conditions (18), and Gm10768 expression levels were elevated in these two settings.…”
Section: Discussionmentioning
confidence: 99%
“…We then analyzed the expression levels of several miRNAs, which were already known as gluconeogenic regulators (15)(16)(17)(18)(19)(20)(21), in mouse hepatocytes infected by Ad-Gm10768, in order to screen the potential target of Gm10768. Among all these miRNAs, only miR-214 and miR-22 were significantly decreased in response to Gm10768 overexpression ( Fig.…”
Section: Gm10768mentioning
confidence: 99%
“…Increasing evidence showed that miR-22 participated in kinds of disease, such as cancer, diabetes [22], and cardiovascular diseases [23]. Anmad et al report that miR-22 is downregulated in peripheral blood mononuclear cells derived from chronic myeloid leukemia (CML) patients and in CML cell line K562 [24].…”
Section: Cell Physiolmentioning
confidence: 99%
“…A study from Kaur et al showed that in vivo silencing of miR-22-3p by antagomiR administration lowered random as well as fasting glucose levels in diabetic mice. MiR-22-3p antagonism improved glucose tolerance and insulin sensitivity [22].…”
Section: Cell Physiolmentioning
confidence: 99%
“…Dentres os miRNAs que compõem esses clusters, o miR-22-3p possui atividade inibitória sobre WNT descrita na literatura, assim como os miRNAs da família do miR-29 (KAUR et al, 2015;LIANG et al, 2016;SUBRAMANIAN et al, 2014;TAN;CAI, 2013;ZHANG et al, 2014), os quais também apresentam inibição da via de TGFβ (LI et al, 2009). O miR-27a-3p, por sua vez, também é conhecido por inibir a via do TGFβ, agindo sobre a tradução de SMAD2, regulando negativamente a via TGFβ/Activina/Nodal, inibindo assim o efeito positivo de TGFβ sobre NANOG, que pode resultar em perda do status de pluripotência em células humanas (CHAE et al, 2017;FUCHS et al, 2014).…”
Section: Mirnas Induzem Diferenciação Celular Ou Pluripotência Por Mounclassified